Inovasi Teknologi dan Transformasi Digital sebagai Penggerak Daya Saing Ekonomi Indonesia - Stanny S. Rawung; Caryza Amadea Tampil; Jeremia Sinaulan; Ignasius Mangalla; Claudio Lintjewas; Apriani br Kaban; Melia Oktaviani; Afrisya S.I Mantiri; Marchelino J Wungow; Jonathan W G Ngangi (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Digital transformation and technological innovation have become strategic factors in enhancing Indonesia's economic competitiveness, particularly through the digitization of MSMEs, economic platforms, and the strengthening of the national innovation ecosystem. This study uses a qualitative literature review approach, examining academic publications, policy reports, and secondary data from official institutions to analyze the relationship between technological innovation, digitization, and increased productivity and competitiveness. The results show that national internet penetration will increase to 80.66% by 2025, with around 25.29 million MSMEs going digital, and the growth of the digital economy is estimated to reach nearly US100 billion, demonstrating the significant contribution of technology to efficiency, market expansion, and product innovation. However, challenges remain in the form of digital literacy disparities, infrastructure limitations, and human resource readiness. In conclusion, technological innovation and digitalization supported by adequate infrastructure, adaptive regulations, and human capacity development are the main foundations for strengthening the national economy's competitiveness in an inclusive and sustainable manner.